Nutrition:The power of protein - Clark, N. (1996)
Some protein questions and answers concerning the nutrition for athletes, e.g. Why is protein important for athletes? How much protein do athletes need? Do bodybuilders need more protein than runners? Can athletes who choose a vegetarian diet get adequate protein? Where to Find Protein (nutrients and protein content).